Clinical Characteristics and Treatment of Atrial Fibrillation and Heart Failure: a Multicenter Survey - HU Huachao, CHEN Xianya, XIE Siyuan, XIA Zhen, XIAO Hua (Zhongguo quanke yixue, 2023)
Background Atrial fibrillation (AF) is a common clinical tachyarrhythmia with high prevalence, and a predisposing factor of stroke. In addition, it has a causal relationship with heart failure (HF) . Treatment options for AF have changed recently owing to the emergence of new drugs. Many investigations are focused on anticoagulant therapies for AF, but relevant multicenter investigations on AF and HF are rare. Objective To investigate the clinical characteristics and treatment of patients with AF combined with HF in Chongqing, China. Methods A total of 4 011 patients with AF and HF who were discharged from 21 hospitals in Chongqing in 2018 were included. Data were collected through the electronic medical record system of the hospitals, including sex, age, basic comorbid conditions, type of AF, NYHA class, thromboembolism history, bleeding history, Color Doppler echocardiography results, HF type and use of drugs (including antithrombotic drugs, rhythm/ventricular rate-control drugs, ACEIs/ARBs, cardiotonic drugs) . The risk of thromboembolism and bleeding were assessed using admission CHA2DS2-VASc score and HAS-BLED score. Sex, basic comorbid conditions, AF type, NYHA class, admission CHA2DS2-VASc score and HAS-BLED score, left atrial diameter, left ventricular end-diastolic diameter, left ventricular ejection fraction, endpoint events (thromboembolism and bleeding) , HF type, and treatment options were compared across three age groups (<65, 65-75, >75) and across patients by the level of hospitalized hospital (secondary and tertiary) . Results In terms of clinical characteristics, the patients had an average age of (74.0±10.6) years, 2 279 (56.8%) were female. The top three prevalent basic comorbid conditions were coronary heart disease (65.1%) , hypertension (51.0%) , and diabetes (17.5%) . 3 346 (83.4%) patients with nonvalvular atrial fibrillation (NVAF) . NYHA class was Ⅲ and Ⅳ in 3 059 patients (76.3%) , thromboembolism events occurred in 531 patients (13.2%) , and bleeding events occurred in 176 patients (4.4%) . In Color Doppler echocardiography results, The average left atrial diameter was (44.12±9.21) mm. The average left ventricular end-diastolic diameter was (48.45±10.06) mm. The average left ventricular ejection fraction was (54.23±11.94) mm. The main type of HF was HF with preserved ejection fraction, accounting for 66.2%. The average CHA2DS2-VASc score was (3.9±1.5) points, and the admission CHA2DS2-VASc score was positively correlated with age (r=0.589, P<0.001) . The average HAS-BLED score was (1.7±1.0) points. 3 641 (90.8%) patients were at high risk of thromboembolism and 723 (18.0%) patients were at high risk of bleeding. In terms of antithrombotic treatment, the overall prevalence of anticoagulation treatment was 47.1%, warfarin was the main anticoagulant (37.8%) , the prevalence of use of the new oral anticoagulant was only 9.3%. The overall prevalence of antiplatelet treatment was 44.6%, most of them were monoclonal antiplatelet agents (13.2%) . The prevalence of anticoagulation treatment decreased with age (χ2trend=136.502, P<0.001) , but that of antiplatelet treatment increased with age (χ2trend=135.730, P<0.001) . The prevalence of anticoagulation treatment, and use of warfarin and new oral anticoagulants in secondary hospitals was significantly lower than that in tertiary hospitals (P<0.001) . A total of 3 162 (78.8%) patients with atrial fibrillation received ventricular rate control. The prevalence of use of beta-blockers, digoxin and ACEIs/ARBs was 61.6%, 17.6%, and 59.7%, respectively. Conclusion The majority of patients with AF complicated with HF in Chongqing are elderly, and the proportion of women is relatively high. HFpEF is the main type of atrial fibrillation, and the NYHA classification is mainly classⅢandⅣ. Most were at high risk for thromboembolism, but less than 1/4 were at high risk of bleeding. The prevalence of antithrombotic treatmentin all ages and levels of hospitals was unsatisfactory, and there was a large gap between current treatment and guideline recommendations in improving HF. In view of this, hospitalphysicians should increase their awareness and capability of standardized diagnosis and treatmentregarding AF with HF.